Training of preschool profile specialists to work with children with special educational needs - Nataliia Kyrsta (Vasyl Stefanyk Precarpathian National University, 2017)
The article highlights some aspects of training of preschool profile specialists to workwith children with special educational needs in modern kindergartens. The main attention isgiven to determination of the key aspects in work with children with peculiarities ofpsychophysical development. The components of future educators' readiness to work ininclusive education are determined. Key words: professional training, educator, children with special educational needs,components of readiness.